2016
DOI: 10.4102/sajce.v5i3.368
|View full text |Cite
|
Sign up to set email alerts
|

Working with children with special needs in Finnish kindergartens: Professionals and/or specialists?

Abstract: The aim is to investigate the links between job satisfaction of Finnish early childhood professionals (ECPs) and the appreciation they receive for their work, and how these are associated with their competence to work with children with diverse needs and backgrounds. Data was collected via nationwide online survey for practitioners (<em>n</em> = 885) working in Finnish kindergartens. The main findings show that ECPs experience their work as satisfactory and receive appreciation from colleagues, fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…children with disabilities or severe mental health problems) or from various backgrounds (e.g. children who are maltreated or neglected) (Nislin et al 2015). Positive values and a belief in inclusion, which in practice can appear as abilities to meet the needs of all children, can support a sense of belonging for both children and teachers in school contexts.…”
Section: Introductionmentioning
confidence: 99%
“…children with disabilities or severe mental health problems) or from various backgrounds (e.g. children who are maltreated or neglected) (Nislin et al 2015). Positive values and a belief in inclusion, which in practice can appear as abilities to meet the needs of all children, can support a sense of belonging for both children and teachers in school contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Work-related well-being is constructed of job satisfaction, stress, and work engagement (Cumming & Wong, 2019;Orsila, Luukkaala, Manka, & Nygard, 2011). It has also been suggested that experienced appreciation and meaningfulness of work are significant elements of work-related well-being (Nislin, Paananen, Repo, Sajaniemi, & Sims, 2015). Work-related well-being of early childhood professionals can be understood as "a dynamic state, involving the interaction of individual, relational, work-environmental, and sociocultural-political aspects and contexts" (Cumming & Wong, 2019, p. 276).…”
Section: Introductionmentioning
confidence: 99%